Cultural Blindness: The Price We Pay for Theory Neglect in Psychology - Sundararajan, Louise (Research in the social scientific study of religion, 2022)
It is argued that cultural blindness is symptomatic of a culture-free science that contributes to the theory crisis in psychology by privileging automatic inference at the expense of the phenomenon and its subjective interpretations. For illustration, the peer review process of a paper that deviated from the "best practice" of a culture-free science is analyzed to identify the need for psychology to put culture and theory back in the picture, if it is to measure up to its ethical obligations to confront the racial and cultural biases in the profession.